Recombinant short TNF-BD protein from smallpox virus is pharmacologically active in an experimental septic shock model - I. P. Gileva; S. N. Yakubitskiy; I. V. Kolosova; S. N. Shchelkunov (Вавиловский журнал генетики и селекции)
Tumor necrosis factor (TNF) is one among the key cytokines that mediate the immune system to protect humans against viral infections. Throughout evolution, anthropogenic Variola virus (VARV) has developed effective mechanisms to overcome human defense reactions. The viral genome encodes soluble proteins imitating the structure of cellular cytokine receptors. These proteins compete with cellular receptors for cytokine binding, thus blocking the antiviral immune response. In particular, the G2R gene of VARV encodes the TNF decoy receptor, VARV-CrmB protein. This protein consists of N-ended TNF-biding (TNF-BD) and C-ended chemokine binding (Ch-BD) domains. Recombinant VARV-CrmB protein has been produced in insect cells using molecular cloning methods and its TNF neutralizing activity has been shown in vitro and in vivo. To decrease the immunogenicity of this protein, a recombinant plasmid coding for shortened TNF-BD protein of VARV in Escherichia coli cells has been constructed. Using the method of immobilized metal affinity chromatography, recombinant TNF-BD protein corresponding to the TNF-biding domain of VARV-CrmB protein was purified from E. coli cells. The therapeutic potential of TNF-BD was studied using an experimental model of LPS-induced septic shock. After septic shock induction, several doses of recombinant TNF-BD were injected and the mortality of experimental animals was observed during 7 days. All mice not injected with TNF-BD had been dead by day 3 of the experiment, but 30, 40 and 60 % of the experimental animals, who received different TNF-BD doses, survived in a dose-dependent manner. Data obtained demonstrate that recombinant TNF-BD protein is pharmacologically active in the experimental model of LPS-induced septic shock.